Holistic Tourism: A New Norm of the Industry. Issue 4 (2nd October 2017) - Li, Mimi; Wu, Bihu; Guo, Pengcheng
ABSTRACT: During the National Tourism Work Conference of 2016, holistic tourism was proposed by Chairman of the China National Tourism Administration (CNTA). As a national tourism governance framework, holistic tourism constitutes a response to the new development approach put forward by President Xi Jinping and implies that tourism will play a significant role in the national economy. This policy highlight introduces the background of holistic tourism, the measures CNTA adopted to promote this governance framework and existing studies on the topic.